Indication of lethal interactions between a solitary bottlenose dolphin (Tursiops truncatus) and harbor porpoises (Phocoena phocoena) in the German Baltic Sea - Gross, Stephanie; Claus, Philip; Wohlsein, Peter; Kesselring, Tina; Lakemeyer, Jan; Reckendorf, Anja; Roller, Marco; Tiedemann, Ralph (Prof. Dr.); Siebert, Ursula (BMC Zoology, 2020)
Background Aggressive interactions between bottlenose dolphins (Tursiops truncatus) and harbor porpoises (Phocoena phocoena) have been reported in different parts of the world since the late 1990s. In the Baltic Sea, harbor porpoises are the only native cetacean species, while bottlenose dolphins may appear there temporarily. In the fall of 2016, a solitary male photo-identified bottlenose dolphin stayed in the German Baltic Sea of Schleswig-Holstein for 3 months. During that time, the necropsies of the stranded harbor porpoises revealed types of trauma of varying degrees in six animals, which is unusual in this area. The purpose of this study was to determine if the appearance of the bottlenose dolphin could be linked to the trauma of the harbor porpoise carcasses. Results Pathological findings in these animals included subcutaneous, thoracic and abdominal hemorrhages, multiple, mainly bilateral, rib fractures, and one instance of lung laceration. These findings correspond with the previously reported dolphin-caused injuries in other regions. Moreover, public sighting reports showed a spatial and temporal correlation between the appearance of the dolphin and the stranding of fatally injured harbor porpoises. Conclusion Despite the fact that no attack has been witnessed in German waters to date, our findings indicate the first record of lethal interactions between a bottlenose dolphin and harbor porpoises in the German Baltic Sea. Furthermore, to our knowledge, this is the first report of porpoise aggression by a socially isolated bottlenose dolphin.